The Role of Cytokines in Inflammatory Process of Knee Osteoarthritis: Systematic Review - Florencia Christofora Ngantung; Basuki Supartono; Hikmah Muktamiroh (Universitas Wijaya Kusuma Surabaya, 2022)
Osteoarthritis (OA) is a degenerative joint disorder that occurs in cartilage. OA is the main cause of disability in adults and generally characterized by pain to the joints that got pressured. Based on several previous studies, it is known that the incidence of osteoarthritis is correlated with synovial inflammation and that inflammatory cytokines play an important role in the expansion of osteoarthritis. Based on these things, the author intends to conduct a literature study with the aim of knowing the role of cytokines on inflammation in knee osteoarthritis. The research was conducted through PubMed and Science Direct databases. The results of the study showed that cytokines played negative different roles depending on the type of cytokines such as those found in knee OA inflammation. Conclusion: Cytokines have a negative effect because they can disrupt synovial tissue balance, induce catabolic processes, and induce osteoclast differentiation and subchondral bone resorption.